Building a Model to Reconstruct the Hellenistic and Roman Road Networks of the Eastern Desert of Egypt, a Semi-Empirical Approach Based on Modern Travelers' Itineraries. Issue 1 (4th March 2021) - Manière, Louis; Crépy, Maël; Redon, Bérangère
The Egyptian Eastern Desert, the part of the Sahara Desert that connects the Nile and the Red Sea, is rich in natural resources and meshed with multiple networks. The adoption of the camel as the main mode of transportation in the 1st millennium BC, faster and with a greater load capacity than humans or donkeys, dramatically changed the logistics used to cross this difficult terrain. Our objective, therefore, is to understand and reconstruct circulation in the region during Antiquity through location factors and the evolution of roads. For this purpose, a least-cost network specific to camel movements has been created for this arid and mountainous region. The network is based on the reconstructed itineraries of modern travelers (18th and 19th centuries) who crossed the region under similar conditions to ancient ones. These routes and the travelers' diaries have enabled us to analyze the main travel constraints; they provide a set of data to calibrate the different movement factors of camel caravans and to validate the calculated least cost paths. The modeled network takes into account transport infrastructures, navigation conditions in plain areas, difficulties of the terrain surface, and the topographical constraints specific to camels. This methodological paper details our approach from the description of movement factors, their mapping, and their use in least cost algorithms to the creation of a network covering 253 archaeological sites and 204 desert watering places. It aims to provide the archaeological and GIS communities with the method and tools to reproduce itineraries based on the hypotheses of movement and empirical data. For this purpose, the data is available and documented by a data paper.